A study on factors affecting intention to quit among primary school teachers in Malaysia. - Phang, Yi Hui; Tan, Hui Ling; Chan, Zi Qing (2025)
Education is the backbone for supporting the long-term growth of a nation and society. However, teacher shortages have become a growing worldwide concern. Primary school teachers are the most important human capital for developing the future pillars of a country as they provide students with a solid foundation of knowledge and shape their future behavior. Nevertheless, the attrition rate of Malaysian primary school teachers is growing from year to year. It is crucial to address this issue so that Malaysia can retain competent primary school teachers and thereby improve education quality. Therefore, the goal of this study is to analyze the factors that influence the intention to quit among Malaysian primary school teachers. We investigate the relationship between burnout, pay, organizational commitment and self-efficacy with intention to quit. This study utilized quantitative research method by collecting questionnaires from 400 primary school teachers in Selangor, Johor, Perak and Kedah. After that, the data were analyzed using Statistical Package for Social Sciences (SPSS). The Pearson Correlation Coefficient was adopted in this study to assess the association between the four independent variables and teachers’ intention to quit. The findings showed that there is a significant positive relationship between teacher burnout and their intention to quit. Moreover, pay, organizational commitment and self-efficacy are significantly and negatively correlated to intention to quit. As a result, the Ministry of Education, school administrators and NUTP must take proactive strategies in addressing the shortage of primary school teachers so that Malaysia can retain qualified teachers and maintain an effective education system.